Efektivitas Partisipasi Masyarakat Dalam Pengelolaan Keuangan Daerah Melalui CBT Pulau Penyengat Provinsi Kepulauan Riau - Putri, Ririn Deswita; N, Nabila; Wandarizqa, Nabila Putri; Simbolon, Lamtio Oktafiana BR; Pangestoeti, Wahjoe (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Background/Problem: This study refers to the phenomenon of public service to understand the important role of society in a reference that can increase trust so that active involvement aims to be able to help manage funds involving the government so that supervision can be accounted for. Method: This study uses a qualitative method with a literature study approach that develops the discussion of previous research on the concept of history produced by attaching photographs as credible supporters to make the actual facts. Results/Findings: The discovery of tourism-based participation in managing local funds contributes to innovative state financial management in understanding communication networks based on the Principles of E-Governance. In the discovery of innovation that gives birth to a million potentials by utilizing historical heritage, traditions to culinary that attract the attention of the community, it can become the main attraction for foreign visitors so that it is able to build a participatory approach to produce a community involvement process that embraces openness between one and another. Conclusion: Community Based Tourism (CBT) is an innovation that is produced in reaching superior participation to ensure that state financial management can be sourced from various sectors. By involving a participatory approach to prioritize the main priorities involving all levels of society in the framework of government performance accountability in managing regional finances.